A critique of the revised Conflict Tactics Scales-2 (CTS-2) - Jones, Richard Toby; Browne, Kevin; Chou, Shihning (Elsevier Masson, 2017)
The purpose of this review is to critically evaluate the Conflict Tactics Scales-2, a measure used worldwide for research and clinical practices. The reliability, validity and normative samples of the CTS-2 are considered and compared with similar psychometric measures. The limitations of the original CTS have been discussed alongside the CTS-2. Reliability is considered to be good to excellent by alpha coefficient and the variance explained by differing samples or methods of administration. Caution is recommended when interpreting the CTS-2 in clinical settings. Researchers point toward a five-factor structure to the CTS-2. The importance of appropriate norms is discussed and considered crucial when using the tool in settings where reporting patterns may differ. Difficulties in comparing CTS-2 scores across samples, cultures and countries are highlighted. Overall, the CTS-2 is a robust psychometric measure, although it holds limited clinical utility if it is used separately from other sources of information gathering (i.e. psychometric measures or interview). In order to enhance clinical utility, it should be administered alongside measures or clinical interviews that can provide added context regarding violence in the family. More research is required in diverse population samples, cultures/countries and languages.